Morphological Characteristics and Spatial Distribution of Seagrass at Batu Kotak Beach, Central Lombok - Novia Intan Cahyani Cahyani; Windiarti Pratiwi Putri; Lalu Syukran Muhsin; Ratna Permata Sari; Maulana David Prayoga; Febrisa Indri Utami (Yayasan Siti Widhatul Faeha, 2025)
Seagrass ecosystems play an important role in coastal ecology, but their presence requires systematic monitoring in the Mandalika coastal area. This study aims to identify the morphological characteristics and spatial distribution of seagrass species along the coast of Batu Kotak, Central Lombok, Indonesia. The research method used quadrat transects placed perpendicular to the shoreline. The results showed three dominant species including Thalassia hemprichii, Syringodium isoetifolium, and Cymodocea rotundata. T. hemprichii forms dense grasslands in shallow lagoons, while S. isoetifolium shows high tolerance to physical disturbances such as waves, and C. rotundata is adaptive to diverse substrates and currents. It was concluded that the differences in morphology and special distribution reflect the specific ecological response of each species to its environment. The results of the study are expected to inform long-term monitoring, habitat restoration, conservation planning, as well as assessing ecological dynamics and anthropogenic impacts affecting seagrass habitats in coastal tourism areas.